The effect of short-term use of Coenzyme Q10 supplementation on selected physical and physiological characteristics of young male elite wrestlers - Mohammad Mohammadi; Azadeh Naderi; Hojjatollah Siavoshi; Fereshteh Mohammadi; Maryam Panah Abadi (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2021)
Aim: The aim of the present study was to determine the effect of short-term use of Coenzyme Q10 supplementation on selected physical and physiological characteristics of young male elite wrestlers.  Materials and methods: The present study is a quasi-experimental human model which was performed using 20 elite wrestlers young men with an average age of 1 ± 5.18 years, weight 1 ± 35.83 kg, height 8/0 ± 75.1 cm and BMI2 ± 67.26 , subjects were randomly divided into drug and placebo groups, first measured using RAST test (anaerobic performance indices) and Cooper test (aerobic power test), curl up test (local abdominal muscle endurance), Press up test and Chin up (upper body endurance test), then, after six weeks of training, the above tests were performed. The collected data were analyzed using SPSS 21 software. Normalization of groups was first performed by Kolmogorov-Smirnov test and confirmation of homogeneity of variances by Levon's test. Correlated t-test was used to investigate intra-group changes and independent t-test and significance level (p≤0.05) were used to examine inter-group changes. Findings: The results of dependent group t2 test showed a significant difference (p≤0.05) in increasing the amount of changes in the experimental group Aerobic power (6.51 change rate), Maximum power (2.61 change rate), Average power (2.60), Minimum power (2.76 change rate), Fatigue Index (0.46 change rate), Curl up (7.2% Change rate) And Press up (7.7 change rate) in the post-test compared to the pre-test. But there was no significant difference (p≤0.05) in the amount of variables expressed in the control group before and after the Chin up test. Conclusion: The results of this study show that the Q10 supplement can enhance some of the physiological and physiological characteristics of young elite wrestlers.